A Systematic Study of Mechanism of Sargentodoxa cuneata and Patrinia scabiosifolia Against Pelvic Inflammatory Disease With Dampness-Heat Stasis Syndrome via Network Pharmacology Approach - Hu, Luanqian; Chen, Yuqi; Chen, Tingting; Huang, Dan; Li, Shihua; Cui, Shuna (Frontiers in Pharmacology, 2020)
Objective: To investigate the mechanism of Sargentodoxa cuneata (Oliv.) Rehder & E.H.Wilson (SC) and Patrinia scabiosifolia (PS) against Pelvic Inflammatory Disease with Dampness-Heat Stasis Syndrome via network pharmacological approach and experimental validation. Methods: The active compounds with OB ≥ 30% and DL ≥ 0.18 were obtained from TCMSP database and further confirmed by literature research. The targets of the compounds and disease were acquired from multiple databases, such as GeneCards, CTD and TCMSP database. The intersection targets were identified by Venny software. Cytoscape 3.7.0 was employed to construct the protein-protein interaction (PPI) network and compound-target network. Moreover, GO enrichment and KEGG pathway analysis were analyzed by DAVID database. Finally, CCK-8, Griess assay and a cytometric bead array (CBA) immunoassay were used for experimental validation by detecting the influence of the active compounds on proliferation of macrophage, release of NO and TNF-α after LPS treatment. Results: 9 bioactive compounds were identified from SC and PS. Those compounds corresponded to 134 targets of pelvic inflammatory disease with dampness-heat stasis syndrome. The targets include vascular endothelial growth factor A (VEGFA), von willebrand factor (VWF), interleukin 6 (IL6), tumor necrosis factor (TNF) and nuclear transcription factor 1 (NFκB1). They act on the signaling pathways like advanced glycation end products-receptor of advanced glycation end products (AGE-RAGE), focal adhesion (FA), Toll-like receptor (TLR) and nuclear transcription factor κB (NF-κB). In addition, by in vitro validation, the selected active components of SC and PS such as acacetin, kaempferol, linarin, isovitexin, sinoacutine could significantly inhibit the release of NO induced by LPS, respectively. Moreover, different dose of acacetin, kaempferol, isovitexin and sinoacutine significantly inhibits the TNF-α production. Conclusion: This study provides solid evidence for the anti-inflammatory mechanism of SC and PS against pelvic inflammatory disease with dampness-heat stasis syndrome, which will provide a preliminary evidence and novelty ideas for future research on the two herbs.